Recording music on location : - Bartlett, Bruce (Elsevier Focal Press, 2007)
From planning on paper to the practical aspects of the set up, this book offers you expert advice on every stage of recording on location. Polish your skills for recording surround sound by following the written and audio examples of different miking techniques.